MLK4 regulates DNA damage response and promotes triple-negative breast cancer chemoresistance - Dawid Mehlich; Michał Łomiak; Aleksandra Sobiborowicz; Alicja Mazan; Dagmara Dymerska; Łukasz M. Szewczyk; Anna Mehlich; Agnieszka Borowiec; Monika K. Prełowska; Adam Gorczyński; Paweł Jabłoński; Ewa Iżycka-Świeszewska; et al. (Cell Death and Disease, 2021)
Abstract Chemoresistance constitutes a major challenge in the treatment of triple-negative breast cancer (TNBC). Mixed-Lineage Kinase 4 (MLK4) is frequently amplified or overexpressed in TNBC where it facilitates the aggressive growth and migratory potential of breast cancer cells. However, the functional role of MLK4 in resistance to chemotherapy has not been investigated so far. Here, we demonstrate that MLK4 promotes TNBC chemoresistance by regulating the pro-survival response to DNA-damaging therapies. We observed that MLK4 knock-down or inhibition sensitized TNBC cell lines to chemotherapeutic agents in vitro. Similarly, MLK4-deficient cells displayed enhanced sensitivity towards doxorubicin treatment in vivo. MLK4 silencing induced persistent DNA damage accumulation and apoptosis in TNBC cells upon treatment with chemotherapeutics. Using phosphoproteomic profiling and reporter assays, we demonstrated that loss of MLK4 reduced phosphorylation of key DNA damage response factors, including ATM and CHK2, and compromised DNA repair via non-homologous end-joining pathway. Moreover, our mRNA-seq analysis revealed that MLK4 is required for DNA damage-induced expression of several NF-кB-associated cytokines, which facilitate TNBC cells survival. Lastly, we found that high MLK4 expression is associated with worse overall survival of TNBC patients receiving anthracycline-based neoadjuvant chemotherapy. Collectively, these results identify a novel function of MLK4 in the regulation of DNA damage response signaling and indicate that inhibition of this kinase could be an effective strategy to overcome TNBC chemoresistance.